IMPLEMENTATION OF NO SMOKING AREA IN THE CAMPUS AREA POLITEKNIK INDONESIA - Tenriawi, Westy (Homes Journal: Hospital Management Studies Journal, 2022)
Background: The World Health Organization (WHO) has offered a strategy to overcome the problems caused by smoking, namely with six MPOWER "Cost-Effective" policy intervention packages to control cigarette consumption, The Regional Government is obliged to establish a smoke-free area in its territory. The Non-Smoking Zone is the responsibility of all components of the nation, both individuals, communities, parliaments and governments to protect current and future generations. Objective:The object of this research is the Indonesian Polytechnic campus by involving students and campus administrators Method : This research method is qualitative with purposive sampling design with a total sample of 5 informants Result : The results of this study obtained 5 informants on the variables of communication, resources, and dispositions that have been running but on the variables of the bureaucratic structure it has not been effective because it is still in the adjustment stage for KTR socialization. Conclusion : Based on the results of the research conducted, it can be concluded that the implementation of KTR at the Indonesian Polytechnic has not run optimally and in accordance with existing procedures, there are obstacles and obstacles both externally and internally on campus so that it has not been able to run ideally.